AB0904 Correlation of rapid3 and promis10 in patients with psoriatic arthritis. (12th June 2018) - Ogdie, A.; Nowell, W.B.; Applegate, E.; Gavigan, K.; Venkatachalam, S.; de la Cruz, M.; Flood, E.; Schwartz, E.J.; Romero, B.; Hur, P.
Abstract : Background: In addition to clinician assessment and laboratory tests, patient-reported outcomes (PROs) are important for managing and improving the quality of care in patients with psoriatic arthritis (PsA). The RAPID3 was originally developed for use in patients with rheumatoid arthritis, but it may be used in clinical practice to assess disease activity in patients with PsA. 1 The PROMIS10 is a general (nondisease-specific) PRO instrument that measures physical, mental, and social health. 2 Developed for the general population, PROMIS10 has not yet been specifically validated in PsA. Objectives: To evaluate the relationship between RAPID3 and PROMIS10 in patients with PsA. Methods: US adults with a self-reported diagnosis of PsA were recruited through CreakyJoints (www.CreakyJoints.org), an online patient support community comprising patients with arthritis and arthritis-related diseases and their caregivers. Respondents completed an online survey that was designed to collect data on socio-demographics and clinical symptoms and included the RAPID3 and PROMIS10 to evaluate disease activity and health-related quality of life (HRQoL), respectively. The RAPID3 consists of three patient self-reported scores (0–10): functional impairment, pain, and patient global assessment; total scores≤3.0=near remission, 3.1 to 6.0=low disease severity, 6.1 to 12.0=moderate disease severity, and ≥12.1 = high disease severity. PROMIS10 is a 10-item survey measuring physical and mental domains; individual scores are transformed to T-score distributions normalised to the general population. PROMIS10 individual scores and global physical and mental health T-scores were stratified by RAPID3 disease severity and compared across RAPID3 severity levels using Kruskal-Wallis or ANOVA tests, respectively. Spearman's correlation coefficient was calculated between RAPID3 total score and the PROMIS10 physical health and mental health T-scores, respectively. Results: Among 203 respondents, the mean (SD) age was 51.6 (10.8) years and 172 (84.7%) were female. The mean (SD) cumulative RAPID3 score was 14.7 (5.8) with mean (SD) functional impairment, pain tolerance, and patient's global estimate scores of 3.3 (1.8), 6.0 (2.3), and 5.4 (2.5), respectively. Patients' mean (SD) PROMIS10 global physical and mental health T-scores were 36.4 (7.3) and 40.2 (9.3), respectively. The mean individual domain scores and global T-scores worsened with increasing RAPID3 disease severity levels (all p < 0.001) (table 1). PROMIS10 physical and mental health T-scores showed a strong (r s =−0.84) and moderate correlation (rs =−0.57) with RAPID3, respectively. Conclusions: RAPID3 and PROMIS10 physical health T-scores were strongly correlated in patients with PsA. PROMIS10 mental health scores moderately correlated with RAPID3, suggesting the mental health questions add a different construct. PROMIS10 and RAPID3 are relatively short questionnaires that can be used in the real world to track and monitor disease symptoms and HRQoL in patients with PsA. References: [1] Orbai A-M, Ogdie A. Rheum Dis Clin North Am. 2016;42(2):265–83. [2] Hays RD, et al. Qual Life Res. 2009;18(7):873–80. Acknowledgements: This study was sponsored by Novartis Pharmaceuticals Corporation, East Hanover, NJ. Disclosure of Interest: A. Ogdie Grant/research support from: Pfizer and Novartis, Consultant for: Abbvie, BMS, Eli Lilly and Company, Novartis, Takeda, and Pfizer, W. B. Nowell Employee of: Global Healthy Living Foundation, E. Applegate: None declared, K. Gavigan Employee of: Global Healthy Living Foundation, S. Venkatachalam Employee of: Global Healthy Living Foundation, M. de la Cruz Employee of: ICON, E. Flood Employee of: ICON, E. Schwartz Employee of: ICON, B. Romero Employee of: ICON, P. Hur Employee of: Novartis Pharmaceuticals Corporation